Acoustic Micro-Tapping Optical Coherence Elastography to Quantify Corneal Collagen Cross-Linking - Kirby, Mitchell A.; Pelivanov, Ivan; Regnault, Gabriel; Pitre, John J.; Wallace, Ryan T.; O’Donnell, Matthew; Wang, Ruikang K.; Shen, Tueng T. (Ophthalmology science (Online), 2023)
To evaluate changes in the anisotropic elastic properties of ex vivo human cornea treated with ultraviolet cross-linking (CXL) using noncontact acoustic micro-tapping optical coherence elastography (AμT-OCE). Acoustic micro-tapping OCE was performed on normal and CXL human donor cornea in an ex vivo laboratory study. Normal human donor cornea (n = 22) divided into 4 subgroups. All samples were stored in optisol. Elastic properties (in-plane Young’s, E, and out-of-plane, G, shear modulus) of normal and ultraviolet CXL–treated human corneas were quantified using noncontact AμT-OCE. A nearly incompressible transverse isotropic model was used to reconstruct moduli from AμT-OCE data. Independently, cornea elastic moduli were also measured with destructive mechanical tests (tensile extensometry and shear rheometry). Corneal elastic moduli (in-plane Young’s modulus, E, in-plane, μ, and out-of-plane, G, shear moduli) can be evaluated in both normal and CXL treated tissues, as well as monitored during the CXL procedure using noncontact AμT-OCE. Cross-linking induced a significant increase in both in-plane and out-of-plane elastic moduli in human cornea. The statistical mean in the paired study (presurgery and postsurgery, n = 7) of the in-plane Young’s modulus, E=3μ, increased from 19 MPa to 43 MPa, while the out-of-plane shear modulus, G, increased from 188 kPa to 673 kPa. Mechanical tests in a separate subgroup support CXL-induced cornea moduli changes and generally agree with noncontact AμT-OCE measurements. The human cornea is a highly anisotropic material where in-plane mechanical properties are very different from those out-of-plane. Noncontact AμT-OCE can measure changes in the anisotropic elastic properties in human cornea as a result of ultraviolet CXL. Proprietary or commercial disclosure may be found after the references.